Modifying lipids for use in food - Gunstone, F. D. (Woodhead Publishing in food science, technology, and nutrition., 2006)
Oils and fats have a major impact on the nutritional and sensory quality of many foods. Food manufacturers must often modify lipid components or ingredients in food to achieve the right balance of physical, chemical and nutritional properties. Modifying lipids for use in foods reviews the range of lipids available, techniques for their modification and how they can be used in food products. Part one reviews vegetable, animal, marine and microbial sources of lipids and their structure. The second part of the book discusses the range of techniques for modifying lipids such as hydrogenation, fractionation and interesterification. Finally, part three considers the wide range of applications of modified lipids in such areas as dairy and bakery products, confectionary and frying oils. With its distinguished editor and international range of contributors, Modifying lipids for use in foods is a standard reference for dairy and other manufacturers using modified lipids. Reviews the range of lipids availableAsseses techniques for modifying lipids such as fractionation and interesterificationConsiders the wide range of applications of modified lipids.